SOSIALISASI IDE BISNIS SANTRI PONDOK PESANTREN SALAF AL-QUR'AN (PPSQ) ASY-SYADZILI KABUPATEN MALANG - Magdalena, Marlina (Universitas Muhammadiyah Malang, 2021)
Entrepreneurship development for Islamic boarding school students is now a necessity, especially for the salafiyah Islamic boarding schools. After graduating from the Islamic boarding school, the challenge for salafiyah pesantren santri is finding work. It's just that salafiyah Islamic boarding school graduates are only provided with religious education, not including general education. This causes the pesantren students to compete hard for jobs, because they do not have the idea to start their own business. Becoming an entrepreneur is one solution for salafiyah boarding school students. Before becoming entrepreneurs, it is necessary to socialize what business ideas are suitable for students, especially to increase readiness and interest in entrepreneurship where this service is through demonstrations and practices. So that it can create business opportunities in the future.